Electrochemical properties of kenaf-derived activated carbon electrodes under different activation time durations for supercapacitor application - Muhammad Nizam Abdul Razak; Zulkarnain Ahmad Noorden; Farid Nasir Ani; Zulkurnain Abdul Malek; Jasrul Jamani Jamian; Nouruddeen Bashir (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The electrochemical properties of supercapacitors with kenaf-derived activated carbon electrodes under different activation time durations were evaluated. The study aims to determine the optimum activation time required that contributes to highest supercapacitor’s perfomance. Kenaf fibre was firstly carbonized at 400 °C to remove its water content and any volatile substances. The resulted kenaf-derived carbon was then impregnated in potassium hydroxide (KOH) with 4:1 impregnation ratio and left overnight. After the impregnation process, the carbon sample was activated at 600 °C with different heating time durations of 1, 2, 3 and 4 hours and named as A600-1, A600-2, A600-3 and A600-4, repectively. Four supercapacitors with the kenaf-derived activated carbon samples as the electrodes were fabricated based on two-electrode symmetrical test cell system. Specific capacitances of 108, 189, 242, and 126 F/g for supercapacitors with activated carbon A600-1, A600-2, A600-3 and A600-4 electrodes, respectively were achieved. These were much higher than previously reported values of only up to 37 F/g. The finding suggests that an inexpensive fibrous carbon material derived from kenaf by a facile pyrolysis process may be a remarkable choice to construct high performance supercapacitor.